Design and initial results of a programme for routine standardised longitudinal follow-up after congenital heart surgery. (2nd February 2017) - Pasquali, Sara K.; Ravishankar, Chitra; Romano, Jennifer C.; Kane, Kristin; Viers, Suzanne; Kennedy, Andrea; Burnham, Nancy; Lowery, Ray; Uzark, Karen; Retzloff, Lauren; Rome, Jonathon J.; Rossano, Joseph W.; et al.
Abstract: Background: With improvements in early survival following congenital heart surgery, it has become increasingly important to understand longer-term outcomes; however, routine collection of these data is challenging and remains very limited. We describe the development and initial results of a collaborative programme incorporating standardised longitudinal follow-up into usual care at the Children's Hospital of Philadelphia (CHOP) and University of Michigan (UM). Methods: We included children undergoing benchmark operations of the Society of Thoracic Surgeons. Considerations regarding personnel, patient/parent engagement, funding, regulatory issues, and annual data collection are described, and initial follow-up rates are reported. Results: The present analysis included 1737 eligible patients undergoing surgery at CHOP from January 2007 to December 2014 and 887 UM patients from January 2010 to December 2014. Overall, follow-up data, of any type, were obtained from 90.8% of patients at CHOP (median follow-up 4.3 years, 92.2% survival) and 98.3% at UM (median follow-up 2.8 years, 92.7% survival), with similar rates across operations and institutions. Most patients lost to follow-up at CHOP had undergone surgery before 2010. Standardised questionnaires assessing burden of disease/quality of life were completed by 80.2% (CHOP) and 78.4% (UM) via phone follow-up. In subsequent pilot testing of an automated e-mail system, 53.4% of eligible patients completed the follow-up questionnaire through this system. Conclusions: Standardised follow-up data can be obtained on the majority of children undergoing benchmark operations. Ongoing efforts to support automated electronic systems and integration with registry data may reduce resource needs, facilitate expansion across centres, and support multi-centre efforts to understand and improve long-term outcomes in this population.